2014
DOI: 10.1155/2014/795745
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Test Parameters on the Friction Behaviour of Anodized Aluminium Alloy

Abstract: The tribological behaviour of anodic oxide layer formed on Al5754, used in automotive applications, was investigated against test parameters. The friction coefficient under different normal loads, sliding speeds, and oxide thicknesses was studied using a pin on disc tribometer. Results show that the increase of load and sliding speed increase the friction coefficient. The rise of contact pressure and temperature seems to cause changes in wear mechanism. Glow-discharge optical emission spectroscopy (GDOES) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
3
9
0
Order By: Relevance
“…This was probably a result of the higher value of surface roughness parameter Ra and also lower value of the thickness coating. This suggestion is in good agreement with Yerokhin et al [28] which found that the hardness decreases when going to the outer part of the oxide coating and also with [29,30] which reported that anodic oxide layers with low thicknesses seem to be more effective in terms of friction. The behavior of the sample No 5 can be explained in a similar way but relatively low friction coefficient could be explained by the low value of surface roughness parameter Ra.…”
Section: The Influence Of Technology Parameters On Friction Coeflcientsupporting
confidence: 89%
“…This was probably a result of the higher value of surface roughness parameter Ra and also lower value of the thickness coating. This suggestion is in good agreement with Yerokhin et al [28] which found that the hardness decreases when going to the outer part of the oxide coating and also with [29,30] which reported that anodic oxide layers with low thicknesses seem to be more effective in terms of friction. The behavior of the sample No 5 can be explained in a similar way but relatively low friction coefficient could be explained by the low value of surface roughness parameter Ra.…”
Section: The Influence Of Technology Parameters On Friction Coeflcientsupporting
confidence: 89%
“…Other studies reported in the literature from Yerokhin et al [53] and Guezmil et al [54] reported that anodic oxide coatings with low thicknesses are more effective in terms of friction, scratch and impact resistance. From the results highlighted in this paper, in terms of wear rate the GHA10 samples shows to have the best overall performance while sliding against the ceramic counterbody, since wear volume was so small to make the wear rate negligible.…”
Section: Discussionmentioning
confidence: 91%
“…This increase showed itself with a sudden increase in uncoated samples. The differences observed in the friction coefficient values can be considered to be related to the changes in the wear morphology [19]. These increases in the friction coefficient can be clarified by the increase in the actual contact area after the running-in phase.…”
Section: Coefficient Of Frictionmentioning
confidence: 99%
“…They observed that composite anodization had a significant beneficial effect in reducing the wear rate. Guezmil et al [19] investigated the tribological behavior of Al5754 aluminum alloy as a result of an anodic coating. In their tests the on pin-ondisc device, the effects of sliding speed, test loads and oxide thickness on friction coefficient values were investigated.…”
Section: Introductionmentioning
confidence: 99%